PENGUATAN SIKAP NASIONALISME MASYARAKAT MELALUI PAGELARAN REYOG (Studi kasus di Desa Bungkal, Kab. Ponorogo) - Triyanto Triyanto (Sekolah Tingi Keguruan dan Ilmu Pendidikan (STKIP) PGRI Tulungagung, 2020)
This study aims to explain the effectiveness of programs carried out by the Government of the Regency of Ponorogo in strengthening the nationalism attitude of the people of the Ponorogo Regency. This research adopted a qualitative approach. The data were gathered by interview, observation, and study of documents. Informants were selected by purposive sampling. Secondary data were gathered from books, articles, and other literature studies. Data were validated by triangulation. The data were analyzed by an interactive model of analysis techniques. This research was located in the Ponorogo Regency, which is the origin of Reyog Ponorogo performing arts. This research was conducted in March 2019. The results are the formation of attitudes; in this case, the attitude of nationalism in local communities. National value-added originates from the values of local wisdom contained in Reyog art, which can help shape the nationalism of rural communities such as a sense of accountability, cooperation, cooperation, mutual support and respect, pride and love for its culture, and foster a spirit of nationalism in each other.